Residual Effect of Nutrient Management Practices in Hybrid Rice under Sri on Growth and Yield of Greengram (Vigna radiata L.) in Rice-greengram Cropping System - Dash, A. C.; Saren, B. K.; Roul, P. K. (International Journal of Bio-resource and Stress Management, 2017)
The field experiments were conducted to study the residual effect of nutrient management practices of kharif rice on growth and yield of rabi greengram was conducted at Krishi Vigyan Kendra, Balasore Odisha during rabi 2013−14 and 2014−15. The experiment was laid out in RBD during the kharif season with 12 treatments replicated thrice and rabi greengram was grown in the residual fertility in the plots without disturbing the layout. The residual effect of different nutrient management prcatices applied to kharif rice significantly influenced the growth, yield attributes and yield of rabi greengram. Growth attributes viz. Plant height, number of branches, dry matter accumulation and number of nodules per plant showed significant improvement due to combined application of nutrients from organic and inorganic sources. Application of 75% N through chemical fertilizers along with 25% N through vermicompost to preceding kharif rice had significant residual effect on rabi grrengram and recorded significantly higher seed yield (959 kg ha-1) and stover yield (2753 kg ha-1)